The Role of Teacher and Pupil in the Context of Autonomous Learning - Jana Kucharová (Theology and Philosophy of Education)
The paper offers a brief overview of the role of teacher and pupil in the context of autonomous learning. An autonomous pupil means an active pupil. His activity consists not only in motivation to learn, but also in participating in social processes, defining one’s own goals and responsibly managing the way to achieve them. The teacher accompanies the active student through the learning process as a manager, mediator, advisor, but also as a fellow pupil. The aim of the paper is to specify the roles and characteristic features of the autonomous teacher and pupil and to point out their differences with respect to the traditional perception of the teacher and pupil in the process of upbringing and education.